QCD resummation for hadronic final states. (11th September 2015) - Luisoni, Gionata; Marzani, Simone
Abstract: We review the basic concepts of all-order calculations in quantum chromodynamics (QCD) and their application to collider phenomenology. We start by discussing the factorization properties of QCD amplitudes and cross-sections in the soft and collinear limits and their resulting all-order exponentiation. We then discuss several applications of this formalism to observables which are of great interest at particle colliders. In this context, we describe the all-order resummation of event-shape distributions, as well as observables that probe the internal structure of hadronic jets.